PICTURE AND PICTURE LEARNING MODEL USING TIME CLOCK MEDIA MATERIALS IN CLASS 3 OF PRIMARY SCHOOL - Hery Setiyawan (IAIN Ambon, 2021)
The following research was carried out in order to describe the increase in the score of mathematics learning outcomes by practicing the picture and picture learning through mock-clock media about time calculations. In the third grade student learning outcomes of SD Kartika IV-9 Surabaya, it was recorded that 52% of students had incomplete scores. The consideration taken by the researcher in determining the solution to the problem is to use the picture and picture learning model through mock-watch media. Artificial hour learning media on theme 6 is applied to class III semester 2. Artificial hours made in learning 5 sub-theme 1 include time calculations. The Artificial Clock is adjusted based on the calculation of time. In addition, the layout of the numbers on the clock must be correct so that it looks like the real one. The subjects chosen in the study were students in class III SD Kartika IV-9 Surabaya. It can be seen from the results of the analysis that shows a difference in student learning outcomes for mathematics subject matter 6 class III SD Kartika IV-9 Surabaya. The difference is shown by the learning result test score at the end of the first cycle is 47% and at the end of the second cycle it is obtained 81%, an increase of 34%. The conclusion that can be drawn is that the application of the picture and picture learning through mock-watch media improves learning outcomes.